Territorial Distribution of Kazakhstan’s Knowledge-Intensive Sectors of the Economy: Opportunities and Prospects - F. M. Dnishev; F. G. Alzhanova; Z. T. Satpayeva (Экономика: стратегия и практика)
The key strategic priorities of the development of Kazakhstan are diversification, technological modernization and formation of a new industrial structure. It is clear that modern industrial structure is impossible to be formed with-out knowledge-based industries and fields, and prerequisites for their development in the regions of Kazakhstan differ significantly.   The goal of this article is to assess the prerequisites and prospects of spatial development of knowledge-based sectors of Kazakhstan’s economy. The methodology of the article is based on the theoretical and methodological provision that possibilities for the development of knowledge-based economy in local territories and at certain points depend of specific factors such as availability of research and academic organizations in the territory. System-structural and functional approaches, methods of empirical research, including observation, comparison, generalization, systematization, methods of analysis and synthesis, logical analysis, methods of regional studies, and cluster analysis were used. There was used as the information base of the research the data reflected in the periodical press, the data of ministries, works of scientists of Kazakhstan and copyright developments under the framework of the study of innovation localization process and knowledge-based sectors of the economy. It is shown that development of knowl-edge-based sectors of economy in Kazakhstan will not be widespread, but will have a «cellular nature», located inside the boundaries of separate territories or «high-tech districts» (knowledge-based hubs, knowledge-based clusters, and smart cities) and perspectives of their development will be considered. The results of the research have been tested while recommendations development on issues of Kazakhstan territories’ technological modernization.